Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Corrigendum to “Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China” [Food Res. Int. 242 (2026) 120014] - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Building damage-matched ground motion generation method using physics-guided generative adversarial networks - Qingle Cheng; Haotian Ren; Hongyu Zhao; Aiqun Li; Linlin Xie (Engineering Structures, 2026)

Synergistic interaction between lead and cadmium via metal-transporter gene upregulation in mice - Tingting Zhang; Weiqin Xing; James A. Ippolito; Shuangshuang Shao; Xinjun Huang; Yongqiang Yang; Linlin Zhao; Yongxia Cheng; Liping Li (BioMetals, 2026)
This study investigated the potential synergistic interactions between Pb and Cd, and assessed the contribution of transporter gene expression to the synergism. Mice were administered varying doses of Pb (15, 30 and 108 mg kg −1 ) or Cd (1, 2 and 3 mg kg −1 ), or a combination of both in the feed. Liver, kidney and bone samples were analyzed for Cd, Pb, Cu, Mn, Zn and Fe concentrations. For treatments exhibiting synergistic effects, the relative expression levels of the divalent metal transporter 1 ( Dmt1 ), ZRT-IRE-like protein 8 ( Zip8 ) and Zip14 were quantified in the liver and kidney using Quantitative Real-Time Reverse Transcription Polymerase Chain Reaction (qRT-PCR). At 108 mg kg −1 Pb , increasing Cd doses from 0 to 1 mg kg −1 significantly increased Pb concentrations in the kidney, liver and bone by 10.6, 60.2 and 19.6%, respectively; concurrently, the relative expression of the Zip8 in the kidney increased by 69.5%, while Dmt1 and Zip14 expression in the liver increased by 79.0 and 85.6%, respectively. At Cd doses ≥ 1 mg kg −1 , increasing Pb rate resulted in elevated Cd concentrations in the kidney, liver and bone; however, no significant changes in transporter expression levels were observed in the kidney under these treatments, possibly due to the upregulation of transporter genes in the intestines. Results demonstrate that interactions between Pb and Cd can be synergistic, and upregulation of certain transporter genes were responsible for such synergism. These findings offer important insights for mitigating the health risks associated with heavy metal exposure in animal and humans.

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Genomics-driven risk assessment of antimicrobial resistance: Current status, challenges, and future perspectives - Peipei Cheng; Qian Wang; Wanting He; Xueyuan Zhu; Yu Cheng; Linlin Xiao; Qingli Dong (Food Research International, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

Ambient-temperature hydrogen storage kinetics of magnesium-based composites enabled by acetone-assisted ball milling and TiF3 catalysis - Linlin Zhang; Qingyun Shi; Chunmin Zhang; Bingbing Chen; Chunli Wang; Limin Wang; Yong Cheng (Fuel, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

Mechanisms of broadband force generation and efficient prediction for a pump-jet propulsor - Jianwei Zhang; Xinli Jin; Jianping Cheng; Duo Xiang; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Fabrication of aramid nanofiber/silver nanoparticles composite aerogels for enhanced electromagnetic interference shielding - Mingyan Wang; Linlin Cheng; Jinxiao Hou; Shaojuan Chen; Liang Jiang; Yanfen Zhou (Chemical Engineering Journal, 2026)

Data-driven method for seismic response prediction of rocking rigid bodies in buildings using deep neural networks - Qingle Cheng; Zhengxuan Song; Linlin Xie; Yuan Tian (Earthquake Engineering and Engineering Vibration, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

Rapid seismic response prediction method of regional buildings under mainshock-aftershock sequence based on deep learning - Qingle Cheng; Hongyu Zhao; Xiangchi Meng; Linlin Xie; Yuan Tian (Bulletin of Earthquake Engineering, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

The role of microplastics in bioavailability and toxicity of triclosan in the soil-earthworm system: Inhibitor or facilitator - Xian Chen; Jingcheng Liang; Linlin Shi; Shipeng Luo; Rong Ji; Jiehong Cheng; Ying Wu; Yuchen Wang (Journal of Environmental Chemical Engineering, 2026)

DMSO intercalation tunes antibiofouling properties of MXene/PVDF composite membranes: Toward sustainable wastewater treatment - Chenhong Cheng; Yuanyuan Zhang; Haochuan Yang; Jie Zhang; Linlin Yang; Rubing Dong; Jiayi Cui; Yongli Qin; Xueye Wang; Xingran Zhang; Jinxing Ma; Junjian Zheng (Journal of Environmental Chemical Engineering, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

A nanoengineered strategy combining deep oxygenation and immunogenicity regulation to unleash the power of anti-tumor immunity - Gang Cheng; Linlin Tao; Nian Huang; Xiaoxiao Hu; Mengmeng Yang; Fangnan Lv; Nan Yang; Siyuan Meng; Zuhang Xing; Boyu Gu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Numerical Simulation of Gas Production and Geomechanical Response of Heterogeneous Gas Hydrate Reservoirs - Jiuhui Cheng; Shuitao Zhang; Linlin Wang; Guangjin Chen (Natural Resources Research, 2026)

Dynamic Mechanisms of Land Use Conflict Under Main Function Oriented Zone Planning: A Case Study of Beijing-Tianjin-Hebei Region - Yang Zheng; Linlin Cheng; Junqi Wang; Yifang Wang; Huizhen Cui (Chinese Geographical Science, 2026)

Carbonized polymer dots as drivers of modernization in Chinese Herbal Medicine - Linlin Zhang; Ying Cheng; Xin Yang; Xiaoyu Chang; Siyu Lu; Bai Yang; Xiaoli Qu (Science Bulletin, 2026)

The environmental niche of light purse seine vessels in the Arabian high seas - Shenglong Yang; Linlin Yu; Jiashu Shi; Weifeng Zhou; Tianfei Cheng; Keji Jiang; Yang Dai (Regional Studies in Marine Science, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

From association to mechanism: Prenatal PFAS Co-exposures induces fetal neural tube defects via autophagy-mediated ferroptosis - Yongyan Chen; Qianhui Cheng; Chen Yang; Sainan Li; Hai Lin; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2026)

Harnessing β-glucans for immune regulation: Bridging structural diversity, therapeutic potential, and functional food development - Xue Wang; Linlin Ma; Chen Chen; Lina Ma; Xian Qu; Ai Ren; Yifa Zhou; Hairong Cheng (Carbohydrate Polymers, 2026)

Ultrasensitive, signal-complementary piezo-capacitive pressure sensor for complex physiological monitoring and HMI - Daojian Su; Linlin Jiang; Zijun Pan; Changhong Yang; Chang Liu; Rongxiao Liu; Tong Liu; Xin He; Shifeng Huang; Zhenxiang Cheng (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

Predictive modeling and mechanistic interpretation of single electron transfer reactivity between antibiotics and reactive halogen species - Linlin Dong; Chenxuan Zong; Jiao Qu; Fangyuan Cheng; Ya-nan Zhang (Journal of Hazardous Materials, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Melatonin protects dopaminergic neurons in paraquat-induced Parkinson in rats through PI3K/AKT/Nrf2 pathway - Yanhui Wang; Xin Zhang; Weiliang Zhang; Minging Han; Qiang Jia; Cunxiang Bo; Hua Shao; Linlin Sai; Cheng Peng (Food and Chemical Toxicology, 2025)

Understanding the seasonal variation of the microplastics occurrence and source in the water source: upstream of the Huangpu River in Shanghai as an example - Zhengwen Li; Linlin Qiu; Zhaofeng Song; Kailin Gong; Xinya Gan; Cheng Peng; Xiaoyong Qian (Environmental Research, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

The influence of 2,6-Di-tert-butyl-p-cresol stress on the microalga Phaeodactylum tricornutum and phycosphere bacteria community - Xiao Lu; Jie Liu; Xinfeng Xiao; Jianliang Xue; Dongle Cheng; Linlin Zhang (World Journal of Microbiology and Biotechnology, 2025)

Are the personality measures for laboratory mice applicable for wild rats? - Jiming Cheng; Huimin He; Linlin Zheng; Hongyu Niu; Hongmao Zhang (Behavioral Ecology and Sociobiology, 2025)

Pore structure-dependent adsorption of monochloramine by activated carbon - Xin Cheng; Xiaojun Miao; Linlin Li; Xueyan Xue; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

Ecological restoration orientated application and modification of constructed wetland substrates - Jiapeng Yang; Shuiping Cheng; Yongqiang Wang; LinLin Li; Shaoyong Lu (Environmental Research, 2025)

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

Improving soil structure and function for continuous cropping of sweet melon using microalgae-based biological fertilizer - Linlin Yang; Xiaotong Song; Yanzhang Feng; Xiaoting Qiu; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Algal Research, 2025)

Transfer dynamics of antimicrobial resistance among gram-negative bacteria - Bangjuan Wang; Muhammad Haris Raza Farhan; Linlin Yuan; Yuxin Sui; Jinhua Chu; Xiaohan Yang; Yuxin Li; Lingli Huang; Guyue Cheng (Science of The Total Environment, 2024)

Organotin exposure and DNA methylation in non-syndromic cleft lip and palate: Integrating findings from case-control studies and animal experiments - Yongyan Chen; Qianhui Cheng; Sainan Li; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2024)

Constructing multi-functional carbon-based aerogels for highly efficient photo-thermal desalination and water purification - Yuqian He; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Enrico Drioli; Jun Ma; Xi Quan Cheng (Desalination, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Evaluating the phase evolution of CMIP GCMs for agricultural climate-change impact assessments in China - Linlin Yao; Qian Tan; Guanhui Cheng; Shuping Wang; Bingming Chen (Agricultural and Forest Meteorology, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Integrated proteome and pangenome analysis revealed the variation of microalga Isochrysis galbana and associated bacterial community to 2,6-Di-tert-butyl-p-cresol (BHT) stress - Linke Guo; Shuangwei Li; Dongle Cheng; Xiao Lu; Xinying Gao; Linlin Zhang; Jianjiang Lu (World Journal of Microbiology and Biotechnology, 2024)

Insights into the uptake, accumulation, and metabolism of UV-328 in lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) - Bingru Li; Zhenzhen Yao; Qi Liu; Linlin Guo; Zhihong Ma; Cheng Li (Chemosphere, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Water-dependent effects of biodegradable microplastics on arsenic fractionation in soil: Insights from enzyme degradation and synchrotron-based X-ray analysis - Kailin Gong; Tianzi Liu; Cheng Peng; Ziyi Zhao; Xiang Xu; Xuechun Shao; Xuan Zhao; Linlin Qiu; Wenwen Xie; Qian Sui; Wei Zhang (Journal of Hazardous Materials, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Mitigation measures of storm surge inundation at an onshore aquaculture farm - Linlin Wang; Shikun Hu; Jing-Cheng Han; Peng Hu; Xuan Yu (Journal of Hydrology, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Uptake, accumulation and metabolism of UV-320 in vegetables and its impact on growth and quality - Bingru Li; Zhenzhen Yao; Dizhe Wei; Linlin Guo; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

CO2 methanation reaction over La-modified NiAl catalysts derived from hydrotalcite-like precursors - Linlin Zhou; Xiaoming Guo; Xu Hu; Yaxin Zhang; Jinglin Cheng; Qiangsheng Guo (Fuel, 2024)

Rapid seismic-damage assessment method for buildings on a regional scale based on spectrum-compatible data augmentation and deep learning - Qingle Cheng; Aiqun Li; Haotian Ren; Cheav Por Chea; Wenjie Liao; Linlin Xie (Soil Dynamics and Earthquake Engineering, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

A prospective comparative study on bladder volume measurement with portable ultrasound scanner and CT simulator in pelvic tumor radiotherapy - Fei Bai; Qiuxia Hu; Xiaowei Yao; Ming Cheng; Lina Zhao; Linlin Xu (Physical and Engineering Sciences in Medicine, 2024)
Objective: The consistency of bladder volume is very important in pelvic tumor radiotherapy, and portable bladder scanner is a promising device to measure bladder volume. The purpose of this study was to investigate whether the bladder volume of patients with pelvic tumor treated with radiotherapy can be accurately measured using the Meike Palm Bladder Scanner PBSV3.2 manufactured in China and the accuracy of its measurement under different influencing factors. Methods: A total of 165 patients with pelvic tumor undergoing radiotherapy were prospectively collected. The bladder volume was measured with PBSV3.2 before simulated localization. CT simulated localization was performed when the bladder volume was 200-400ml. The bladder volume was measured with PBSV3.2 immediately after localization and recorded. The bladder volume was then delineated on CT simulation images and recorded. To compare the consistency of CT simulation bladder volume and bladder volume measured by PBSV3.2. To investigate the accuracy of PBSV3.2 in different sex, age, treatment purpose, and bladder volume. Results: There was a significant positive correlation with bladder volume on CT and PBSV3.2 ( r = 0.874; p < 0.001). The mean difference between CT measured values and PBSV3.2 was (-0.14 ± 50.17) ml. The results of the different variables showed that the overall mean of PBSV3.2 and CT measurements were statistically different in the age ≥ 65 years, bladder volumes > 400ml and ≤ 400ml groups ( p = 0.028, 0.002, 0.001). There was no statistical significance between the remaining variables. The volume difference between PBSV3.2 measurement and CT was 12.87ml in male patients, which was larger than that in female patients 3.27ml. Pearson correlation analysis showed that the correlation coefficient was 0.473 for bladder volume greater than 400ml and 0.868 for bladder volume less than 400ml; the correlation coefficient of the other variables ranged from 0.802 to 0.893. Conclusion: This is the first large-sample study to evaluate the accuracy of PBSV3.2 in a pelvic tumor radiotherapy population using the convenient bladder scanner PBSV3.2 made in China. PBSV3.2 provides an acceptable indicator for monitoring bladder volume in patients with pelvic radiotherapy. It is recommended to monitor bladder volume with PBSV3.2 when the planned bladder volume is 200-400ml. For male and patients ≥ 65 years old, at least two repeat measurements are required when using a bladder scanner and the volume should be corrected by using a modified feature to improve bladder volume consistency.

A novel method of identifying estuary high-nutrient zones for water quality management - Linlin Wang; Xiaoyu Lei; Guo Yuehua; Yang Zhou; Jing-Cheng Han; Yuefei Huang; Bing Li; Xian-zhong Mao; Zhaozhao Tang (Science of The Total Environment, 2024)

Microplastics alter Cr accumulation and fruit quality in Cr(VI) contaminated soil-cucumber system during the lifecycle: Insight from rhizosphere bacteria and root metabolism - Kailin Gong; Qi Zhang; Xuechun Shao; Yonghong Wu; Zhihua Qiao; Linlin Qiu; Wei Zhang; Cheng Peng (Science of The Total Environment, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Fabrication and mechanism of La/Al bimetallic organic frameworks for phosphate removal - Zheng Zhu; Linlin Qin; Yulong Liu; Qiqi Zhang; Peng Cheng; Wenyan Liang (Chemical Engineering Journal, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

State-of-the-art analysis of the fuel desulphurization processes: Perspective of CO2 utilization in coal biodesulphurization - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Linlin Wang; Zhaozhao Tang; Yang Zhou; Yuefei Huang (Chemical Engineering Journal, 2023)

Phase Transition in Geomaterials Under Unsaturated Conditions - Jiuhui Cheng; Xuanzhe Xia; Zhiqiang Liu; Linlin Wang (Rock Mechanics and Rock Engineering, 2023)

Integrated analyses delineate distinctive immunological pathways and diagnostic signatures for Behcet’s disease by leveraging gene microarray data - Haoting Zhan; Linlin Cheng; Haolong Li; Yongmei Liu; Yuan Huang; Xiaomeng Li; Songxin Yan; Yongzhe Li (Immunologic Research, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Associations among bisphenol A, its analogs, and chlorinated derivatives in placenta and risk for neural tube defects: A case-control study - Haiyan Zhu; Qianhui Cheng; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2023)

Damping, soft, and thermally conductive composite elastomer via introducing bottlebrush chains - Shipeng Rao; Xiangliang Zeng; Xiaxia Cheng; Jianfeng Fan; Dongyi He; Linlin Ren; Guoping Du; Xiaoliang Zeng (Chemical Engineering Journal, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Synergistic strategy based on mild phototherapy and deep tumor hypoxia reversal comprehensively remodels the tumor microenvironment for improved immunotherapy - Linlin Tao; Gang Cheng; Fangnan Lv; Ruiqi Wang; Nan Yang; Zuhang Xing; Boyu Gu; Siyuan Meng; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

UV-B regulates seasonal greening of albino leaves by modulating CsHY5-inhibiting chlorophyll biosynthesis in Camellia sinensis cv. Huangkui - Xuyang Liu; Xin Cheng; Jingjie Cao; Wenfeng Zhu; Ying Sun; Ning Lin; Xiaochun Wan; Linlin Liu (Plant Science, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Selective recovery of lithium from spent LiFePO4 battery via a self-catalytic air oxidation method - Hao Jin; Jialiang Zhang; Cheng Yang; Linlin Ma; Yongqiang Chen; Chengyan Wang (Chemical Engineering Journal, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Study on antibacterial mechanism of electron beam radiation on Aspergillus flavus - Linlin Fan; Lili Li; Feifei Shang; Yuhua Xie; Zhenhua Duan; Qianwei Cheng; Yuqiao Zhang (Food Bioscience, 2023)

Data quality evaluation and calibration of on-road remote sensing systems based on exhaust plumes - Shijie Liu; Xinlu Zhang; Linlin Ma; Liqiang He; Shaojun Zhang; Miaomiao Cheng (Journal of Environmental Sciences, 2023)

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

Alteration of alpha and beta diversity in nekton community by extreme marine heatwave events: An example from the East China Sea - Zunlei Liu; Linlin Yang; Liping Yan; Hui Zhang; Yi Zhang; Min Xu; Yan Jin; Jiahua Cheng (Frontiers in Marine Science, 2022)
In the year of 2016 to 2017, record-breaking marine heatwave (MHW) events occurred along the Chinese coast, exerting severe impacts on coastal fishes and fisheries. However, the response of the nekton community to MHW events still remains poorly understanding. Thus, to investigate the influences of the MHW events on species composition dynamics, this study conducted a survey on nekton communities in the northern East China Sea in the summers during 2014 to 2017. The recently-developed “heatwaveR” package was adopted to describe the variation characteristics of heatwaves within the study area, based on high-resolution remote-sensing sea surface temperature products. We also compared variations in the community structures of different biological groups before (2014–2015) and during the occurrence of the MHW events (2016–2017). During the MHW events, temperature increased by approximately 2.3°C in both 2016 and 2017. Compared with those before the MHW events, the biomass and dominance of several important crustaceans decreased, and the biomass of warm water affinity species increased significantly, while their richness and diversity decreased; the biomass of warm temperature affinity species declined significantly, while their diversity increased slightly. These results show the difference in the response rates of species with different thermal preferences and different species compositions to the extreme climate change. Beta diversity analysis revealed that the inter-group variation before and during the MHW event exceeded the intra-group variation, proving that MHWs changed the community structure to a certain extent. PERMANOVA test showed that the species compositions of planktivorous fish (FG1) and small-omnivorous fish (FG2) in the feeding-functional groups were significantly different before and during the MHW event, which may be attributed to the impact of MHWs on oligotrophic fishes through thermal preference and the trophic cascade effect. There was no significant change in the species compositions of other functional groups, indicating that medium-trophic and eutrophic fishes possessed certain adaptability to MHWs. Regarding fisheries management under extreme warming events, it would be advisable to diagnose temperature anomalies in the early stage, monitor changes in species abundance in the early life cycle, and then rapidly develop suitable fishing strategies.

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

Identifying Priority Conservation Areas of Largehead Hairtail (Trichiurus japonicus) Nursery Grounds in the East China Sea - Zunlei Liu; Yan Jin; Liping Yan; Yi Zhang; Hui Zhang; Chuyi Shen; Linlin Yang; Jiahua Cheng (Frontiers in Marine Science, 2022)
Identifying the spatio-temporal distribution hotspots of fishes and allocating priority conservation areas could facilitate the spatial planning and efficient management. As a flagship commercial fishery species, Largehead hairtail ( Trichiurus japonicus ) has been over-exploited since the early 2000s. Therefore, the spatio-temporal management of largehead hairtail nursery grounds could effective help its recovery. This study aims to predict juvenile largehead hairtail distribution patterns and identify priority conservation areas for nursery grounds. A two-stage hierarchical Bayesian spatio-temporal model was applied on independent scientific survey data (Catch per unit effort, CPUE) and geographic/physical variables (Depth, Distance to the coast, Sea bottom temperature, Dissolved oxygen concentration and Net primary production) to analyze the probability of occurrence and abundance distribution of juvenile largehead hairtail. We assessed the importance of each variable for explaining the occurrence and abundance. Using persistence index, we measured the robustness of hotspots and identified persistent hotspots for priority conservation areas. Selected models showed good predictive capacity on occurrence probability (AUC = 0.81) and abundance distribution ( r = 0.89) of juvenile largehead hairtail. Dissolved oxygen, net primary production, and sea bottom temperature significantly affected the probability of occurrence, while distance to the coast also affected the abundance distribution. Three stable nursery grounds were identified in Zhejiang inshore waters, the largest one was located on the east margin of the East China Sea hairtail national aquatic germplasm resources conservation zones (TCZ), suggesting that the core area of nursery grounds occurs outside the protected areas. Therefore, recognition of these sites and their associated geographic/oceanic attributes provides clear targets for optimizing largehead hairtail conservation efforts in the East China Sea. We suggested that the eastern and southern areas of TCZ should be included in conservation planning for an effective management within a network of marine protected areas.

Estimation of the SARS-CoV-2 transmission probability in confined traffic space and evaluation of the mitigation strategies - Linlin Chen; Guangze Ban; Enshen Long; Gretchen Kalonji; Zhu Cheng; Li Zhang; Shurui Guo (Environmental Science and Pollution Research, 2021)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Spatiotemporal variability and trends in the hydrology of the Xiang River basin, China: extreme precipitation and streamflow - Juan Du; Linlin Cheng; Qiang Zhang (Arabian Journal of Geosciences, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Reclamation suitability evaluation of damaged mined land based on the integrated index method and the difference-product method - Linlin Cheng; Haiyuan Sun (Environmental Science and Pollution Research, 2019)

Who cares what parents think or do? Observational learning and experience-based learning through communication in rice farmers’ willingness to adopt sustainable agricultural technologies in Hubei Province, China - Yangmei Zeng; Junbiao Zhang; Ke He; Linlin Cheng (Environmental Science and Pollution Research, 2019)

Relative trajectory-driven virtual dynamic occlusal adjustment for dental restorations - Sukun Tian; Ning Dai; Xiaosheng Cheng; Linlin Li; Yuchun Sun; Haihua Cui (Medical & Biological Engineering & Computing, 2019)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

Linkage disequilibrium and functional analysis of PRE1 insertion together with SNPs in the promoter region of IGFBP7 gene in different pig breeds - Qingyan Wu; Hao Yu; Wenzhen Wei; Yunyun Cheng; Shan Huang; Hongyu Shi; Songcai Liu; Jichao Xia; Hongyao Jia; Linlin Hao (Journal of Applied Genetics, 2018)

An integrated approach for water scarcity evaluation—a case study of Yunnan, China - Hongrui Wang; Linlin Fan; Yuan Liang; Cheng Wang (Environment, Development and Sustainability, 2018)

Applicability of TRMM satellite precipitation in driving hydrological model for identifying flood events: a case study in the Xiangjiang River Basin, China - Yumeng Yang; Juan Du; Linlin Cheng; Wei Xu (Natural Hazards, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

TsMIP6 enhances the tolerance of transgenic rice to salt stress and interacts with target proteins - Linlin Sun; Guohong Yu; Xiaori Han; Shichao Xin; Xiaojing Qiang; Linlin Jiang; Shuhui Zhang; Xianguo Cheng (Journal of Plant Biology, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Expression of tomato SlTIP2;2 enhances the tolerance to salt stress in the transgenic Arabidopsis and interacts with target proteins - Shichao Xin; Guohong Yu; Linlin Sun; Xiaojing Qiang; Na Xu; Xianguo Cheng (Journal of Plant Research, 2014)

A KPCA texture feature model for efficient segmentation of RADARSAT-2 SAR sea ice imagery - Linlin Xu; Jonathan Li; Alexander Wong; Cheng Wang (International Journal of Remote Sensing, 2014)

A Critical Role of Src-Suppressed C Kinase Substrate in Rat Astrocytes After Chronic Constriction Injury - Yinyin Xia; Haiou Liu; Aiguo Shen; Yonghua Liu; Linlin Sun; Tao Tao; Qing Ke; Chun Cheng (NeuroMolecular Medicine, 2010)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)

Expression of phytoene synthase gene (Psy) is enhanced during fruit ripening of Cara Cara navel orange (Citrus sinensis Osbeck) - Nengguo Tao; Zhiyong Hu; Qin Liu; Juan Xu; Yunjiang Cheng; Linlin Guo; Wenwu Guo; Xiuxin Deng (Plant Cell Reports, 2007)